2008
DOI: 10.1071/rd08144
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol-induced spermatogenesis requires a functional androgen receptor

Abstract: Spermatogenesis requires androgen but, paradoxically, oestradiol (E2) treatment stimulates spermatogenic development in gonadotrophin- and androgen-deficient hypogonadal (hpg) mice. The mechanisms of E2-induced spermatogenesis were investigated by determining intratesticular E2 levels and testis cell populations in E2-treated hpg male mice, and E2 spermatogenic actions were determined in androgen receptor-knockout (ARKO) mice. Despite increased serum E2 concentrations (150-300 pmol L(-1)), intratesticular E2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Although the high doses of estrogenic substances have a negative impact on testis development and initiation of spermatogenesis [8][9][10], lower doses have a stimulatory effect [10][11][12]. The stimulatory effect of estradiol on spermatogonia number/ /proliferation has been confirmed by recent studies [13,14]. According to studies performed by Jobling et al [15], DEHP is slightly estrogenic, which may explain its stimulatory effect on spermatogonia.…”
Section: Introductionsupporting
confidence: 56%
“…Although the high doses of estrogenic substances have a negative impact on testis development and initiation of spermatogenesis [8][9][10], lower doses have a stimulatory effect [10][11][12]. The stimulatory effect of estradiol on spermatogonia number/ /proliferation has been confirmed by recent studies [13,14]. According to studies performed by Jobling et al [15], DEHP is slightly estrogenic, which may explain its stimulatory effect on spermatogonia.…”
Section: Introductionsupporting
confidence: 56%
“…We previously showed that our genomic ARKO mice have a modest reduction in serum testosterone levels (Notini et al 2005); therefore, their phenotype arises through a combination of loss of genomic AR signaling and testosterone deficiency. However, treatment of genomic ARKO males with supraphysiological levels of testosterone for 6 weeks has no effect on any phenotypic parameter examined ( (Lim et al 2008), and H E MacLean & R A Davey, unpublished data), supporting the hypothesis that the ARKO male phenotype is caused by the loss of DNA-binding-dependent AR actions. Therefore, our study is strongly suggestive that androgens act through the genomic AR signaling pathway to play a physiological role in a number of tissues in both sexes.…”
Section: Discussionmentioning
confidence: 72%
“…The mutual action of FSH and estrogen was also reported in our previous study when concomitant administration of estradiol benzoate and FSH to immature rats resulted in the enhancement of FSH stimulatory effect on the initiation of spermatogenesis by estrogen [21]. Lim et al [40] reported recently that Estimulated spermatogenic development in hpg mice occurred with markedly suppressed intratesticular E levels. Authors suggested that this inducing effect of E on spermatogenesis is caused by extratesticular E actions, predominantly increase in FSH level, what was also suggested before by Ebling et al [41].…”
Section: Discussionmentioning
confidence: 77%